Peritoneal splenosis, simulating carcinomatosis - Sh. V. Timerbulatov; R. R. Akhmerov; M. V. Timerbulatov; V. M. Timerbulatov (Вестник хирургии имени И.И. Грекова)
We presents the clinical case of splenosis of the abdominal cavity, simulating carcinomatosis. Radiation methods (ultrasound, computed tomography, positron emission tomography) revealed multiple soft tissue tumors in the right iliac region, pelvis, bed of the removed spleen. The patient underwent a splenectomy 23 years ago for a spleen injury. Laparoscopy was performed, tumor formations in the right iliac region and pelvis were removed. Histological examination confirmed the diagnosis of splenosis.